Implementing depression care in under-resourced communities: a school-based family resilience skill-building pilot randomized controlled trial in the United States - Marlotte, Lauren; Klomhaus, Alexandra; Ijadi-Maghsoodi, Roya; Aralis, Hilary; Lester, Patricia; Griffin Esperon, Kim; Kataoka, Sheryl (Frontiers in Psychology, 2023)
Youth in under-resourced communities are more likely to have greater social risk factors for mental health needs yet have less access to needed care. School-based mental health services are effective in treating common disorders such as adolescent depression; however, few have a family-centered approach, which may especially benefit specific populations. Utilizing a community-partnered approach, we adapted an established, trauma-informed, resilience skill-building family intervention for adolescents with depression. We conducted a feasibility pilot a in a small randomized controlled feasibility pilot trial of the anan adapted intervention in one a large school district that serves predominately low-income, Latinx students , racially, and ethnically diverse school district in the Southwest United States between 2014-2017. Youth between the ages of 12-18 years old with a Patient Health Questionnaire (PHQ-8) score of 10 or higher, who spoke English or Spanish, were recruited from 12 school mental health clinics. Twenty-five eligible adolescents with depression and their participating caregivers were enrolled and randomly assigned to receive either the adapted intervention, Families OverComing Under Stress for Families with Adolescent Depression (FOCUS-AD), or usual care, Cognitive Behavioral Therapy (CBT) only. Most of the sample was Latinx and female. We evaluated feasibility, acceptability, and preliminary effectiveness. Among participants who completed standardized assessments administered at baseline and approximately five months post-randomization (n=10 FOCUS-AD, n= 11 CBT only), effectiveness was explored by identifying significant changes over time in adolescent mental health within the FOCUS-AD and CBT only groups and comparing the magnitude of these changes between groups. Nonparametric statistical tests were used. We found the FOCUS-AD intervention to be feasible and acceptable; participant retention was high. Adolescent symptoms of depression (measured by the PHQ-8) improved significantly from baseline to follow-up for youth in both FOCUS-AD (median decrease [MD] = 10, p=0.02) and control (MD = 6, p=0.01) groups, with no significant difference across the two groups.Results were similar for symptoms of PTSD (measured by the Child PTSD Symptom Scale;